THE DEVELOPMENT OF CREDIT SYSTEM OF AGRICULTURAL PRODUCTION IN CONDITIONS OF CAPITALISM IN THE STAVROPOL REGION IN THE LATE 19th AND EARLY 20th CENTURY - Tatiana Aleksandrovna Shebzukhova; Galina Nikolaevna Rykun (Современная наука и инновации)
In the late 19th and early 20th century in the agrarian sector of the Stavropol province carried out the transition to a market economy, which required forms of additional funding the production of marketable products. The article reveals some of the characteristics of the credit policy of the State in rural area of Stav-ropol to the accelerated integration of the region into the Russian market.